CBCT analysis of apical distance between second lower premolars, first and second lower molars and mandibular canal - Đeri Aleksandra (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Mandibular canal with the associated neurovascular bundle may be closely related to the apices of man-dibular teeth. In order to avoid injuries and damages to the inferior alveolar nerve during invasive dental procedures, it is important to know its localization. The aim of this study was to determine the average vertical distances of the root apices of second premolars, first molars and second molars mesially and distally from the upper projection of the mandibular canal on the sagittal section of CBCT images, and determine if there were statistically significant differences between the age and gender groups. Material and methods The research was conducted at the Faculty of Medicine of the University of Banja Luka, and the sample consisted of 146 CBCT images of patients. CBCT images were obtained using Planmeca ProMax 3D Mid instrument (Planmeca, Helsinki, Finland) and analyzed using Planmeca Romexis Viewer software. In the sagittal section , the vertical distance from the root apex to the upper projection of the mandibular canal was measured for each examined tooth. Results The distal root of the first molar (4.88 mm) had the greatest average vertical distance of the root apex from the mandibular canal, and the distal root of the second molar had the smallest average vertical distance (2.76 mm). There was statistically significant difference between certain age groups in the values of individual roots, for the second molar mesially and distally (p < 0.05), while for the first molar mesially the value of p was at the limit of significance (p = 0.05). Conclusion The results of this study showed that distal root of the mandibular second molar had the smallest vertical distance from mandibular canal, therefore an extra caution during a root canal treatment and careful planning of oral surgery in this region is recommended.